2008
DOI: 10.1016/j.neuroscience.2007.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal interneurons co-express transcripts encoding the α7 nicotinic receptor subunit and the cannabinoid receptor 1

Abstract: The notion of functional interactions between the α7 nicotinic acetylcholine (α7 nACh) and the cannabinoid systems is emerging from recent in vitro and in vivo studies. Both the α7 nACh receptor and the cannabinoid receptor 1 (CB1) are highly expressed in the hippocampus. To begin addressing possible anatomical interactions between the α7 nACh and the cannabinoid systems in the rat hippocampus, we investigated the distribution of neurons expressing α7 nACh mRNA in relation to those containing CB1 mRNA. By in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 56 publications
(129 reference statements)
1
23
0
Order By: Relevance
“…The delayed SPW-R appearance is due to their masking by serotonin in a dose dependent manner, which compares well to effects on sharp waves in in vivo hippocampal EEG recordings (Richter-Levin and Segal, 1990). The effect was dependent on 5-HT 1A or 5-HT 2A/C receptor activation but insensitive to activation of excitatory 5-HT 3 receptors, which are expressed on subtypes of interneurons (Turner et al, 2004;Morales et al, 1996Morales et al, , 2007Chittajallu et al, 2013).…”
Section: Discussionsupporting
confidence: 55%
“…The delayed SPW-R appearance is due to their masking by serotonin in a dose dependent manner, which compares well to effects on sharp waves in in vivo hippocampal EEG recordings (Richter-Levin and Segal, 1990). The effect was dependent on 5-HT 1A or 5-HT 2A/C receptor activation but insensitive to activation of excitatory 5-HT 3 receptors, which are expressed on subtypes of interneurons (Turner et al, 2004;Morales et al, 1996Morales et al, , 2007Chittajallu et al, 2013).…”
Section: Discussionsupporting
confidence: 55%
“…dopamine and norepinephrine (Hajos and Rogers, 2010). Post-synaptic nAChA7Rs have been found on inhibitory GABAergic interneurons where they facilitate neuronal functioning (Morales et al, 2008). A reduced number of nAChA7Rs might result in reduction of inhibition and a consequent increase in excitability could lead to the deficient sensory and overall inhibition and epilepsy (Stevens et al, 2015) and to cognitive and learning disturbances observed in schizophrenia (Feuerbach et al, 2009).…”
Section: Nacha7r Activation Results In Ca2+ Influx and A Consequent Fmentioning
confidence: 99%
“…CB1R is not expressed in layer 5b of S1. The basal ganglia contain high levels of CB1R (Egertova and Elphick 2000;Herkenham et al 1990;Marsicano and Lutz 1999;Morales et al 2007;Tsou et al 1998) and receive inputs both from somatosensory (S1) and motor (M1) cortices (Alloway et al 2006). The pontine nuclei (Pn), which contain CB1R expressing neurons (Cristino et al 2006), receive inputs from CB1R regions of S1 (layer 5b; Mercier et al 1990) and M1 (layer 5; Legg et al 1989).…”
Section: Cannabinoids Do Not Affect Duration Synchrony and Coordinamentioning
confidence: 99%
“…Whereas the basal ganglia, cerebellum, neocortex, and hippocampus contain high levels of CB1R (Egertova and Elphick 2000;Herkenham et al 1990; Marsicano and Lutz 1999;Morales et al 2007;Tsou et al 1998), CB1R expression in the thalamus and brain stem is relatively sparse . Furthermore, CB1R expression varies along the cortical surface and between cortical layers (Bodor et al 2005;Lafourcade et al 2007).…”
Section: Introductionmentioning
confidence: 99%